Palindromic Rheumatism: Just a Pre-rheumatoid Stage or Something Else? - Sanmartí, Raimon; Frade-Sosa, Beatriz; Morlà, Rosa; Castellanos-Moreira, Raul; Cabrera-Villalba, Sonia; Ramirez, Julio; Salvador, Georgina; Haro, Isabel; Cañete, Juan D. (Frontiers in Medicine, 2021)
Palindromic rheumatism (PR), a unique clinical entity, has a characteristic clinical presentation with a relapsing/remitting course. It is established that most patients with PR evolve to chronic disease, of which rheumatoid arthritis (RA) is by far the most common. The relationship between PR and RA is unclear, with similarities and differences between the two, and not all patients evolving to RA in the long-term. Therefore, PR is clearly a pre-RA stage for most, but not all, patients. Autoimmunity plays a substantial role in PR, with the same characteristic autoantibody profile observed in RA, although with some differences in the immune response repertoire. Autoinflammation may also be relevant in some cases of PR. Prognostic factors for RA progression are identified but their exact predictive value is not clear. There are several unmet needs in PR, such as the diagnostic criteria and clinical case definition, the pathogenic mechanisms involved in the unusual clinical course and the evolution to RA and understanding of the best therapeutic strategy that could avoid progression to persistent and potentially destructive arthritis.